Estudio de Viabilidad para la Implementación de (SW) Software de procesos administrativos en el cuerpo de Bomberos de Jujan. - Pinto Briones, Carlos Enrique (2018)
Nowadays the organizations are oriented to the globalized world and the technological one in the communication and information, some of organizations understand the needs of reformulating and restructuring the way of organizing and adjusting to the new competitive tendencies since these means go together with the technology and the computer science, also these tools are the fundamental pieces in the administrative processes of the companies. For this reason, it was thought to carry out a thorough study of the company and with its collaboration, the Jujan Fire Department, the viability is studied for the future implementation of a software that controls the administrative processes within it, as well seeks to decrease time and also counts on accurate and timely information with quality to improve the functionality of the organization. To develop this case study it is necessary the research and collaboration of the organization, and in turn to identify the feasibility of the problem in the software and estimate the most viable solution at the time of the completion of the software, but also the study of this project It will have several relevant elements such as: implementing the new or collaborative software to the existing one, also avoiding the loss of information. The line of research established for this case study corresponds to the creativity to the ability to create new things is the development of information systems, communication and business and technological enterprises and the Research Subline of a computer system development.